Preparation of Nano Pore ZSM-5 Membranes: Experimental, Modeling and Simulation - Mansoor Kazemimoghadam; Zahra Amiri Rigi (Journal of Water and Environmental Nanotechnology, 2018)
Nano pore ZSM-5type membranes were prepared on the outer surface of a porous-mullite tube by in situ liquid phase hydrothermal synthesis. The hydrothermal crystallization was carried out under an autogenous pressure, at a static condition and at a temperature of 180°C with tetra propyl ammonium bromide (TPABr) as a template agent. The molar composition of the starting gel of ZSM-5 zeolite membrane was: SiO2/Al2O3=100, Na2O/Al2O3=0.292, H2O/Al2O3=40–65, TPABr/ SiO2=0.02-0.05. The zeolites calcinations were carried out in the air at 530°C, to burn off the template (TPABr) within the zeolites. X-ray diffraction (XRD) patterns of the membranes consisted of peaks corresponding to the support and zeolite. The crystal species were characterized by XRD, and morphology of the supports subjected to crystallization was characterized by scanning electron microscopy (SEM). Performance of Nano-porous ZSM-5 membranes was studied for separation of water–unsymmetrical dimethylhydrazine (UDMH) mixtures using pervaporation (PV). Finally, a comprehensive unsteady-state model was developed for the pervaporation of water-UDMH mixture by COMSOL Multiphysics software version 5.2. The developed model was strongly capable of predicting the effect of various dimensional factors on concentration and velocity distributions within the membrane module. The best ZSM-5 zeolite membranes had a water flux of 2.22 kg/m2.h at 27°C. The best PV selectivity for ZSM-5 membranes was obtained to be 55.